Significant enlargement of a specific subset of CD3+CD8+ peripheral blood leukocytes mediating cytotoxic T-lymphocyte activity during human immunodeficiency virus infection. - Bensussan, A (1993)
We have obtained a monoclonal antibody termed BY55 that defines an 80-kDa cell-surface structure on a subset of circulating peripheral blood mononucleocytes. This structure, which was not detected on most cell lines or activated lymphocytes, was expressed exclusively on 15-25% of CD2+ circulating lymphocytes, including a major subset within the CD3- and the T-cell receptor gamma delta + lymphocytes and a small percentage of the CD3+CD8+ cells. Moreover, we have shown that the BY55 molecule delineated the competent killer circulating lymphocytes. In the present report, additional two- and three-color immunofluorescence studies of peripheral blood lymphocytes were done to precisely determine BY55 expression within the T-cell population. In normal individuals, peripheral blood CD3+CD8+BY55+ cells represented only 5-6% of the lymphocytes, and these cells possessed cytolytic activity. Interestingly, we found that the percentage of total BY55+ lymphocytes as well as the percentage of CD3+CD8+BY55+ was significantly increased in peripheral blood lymphocytes of human immunodeficiency virus-seropositive individuals.